Efficient calculation of interior scattering from cavities with small modifications. Issue 2 (1st January 2020) - Chen, Xinlei; Liu, Xiuqiang; Gu, Changqing
Abstract : The analysis of the interior scattering from open cavities with small modifications is an important task in designing a stealthy jet engine. Previous research has shown the magnetic field integral equation with the Kirchhoff approximation can be used to calculate the cavity interior scattering. However, it must repeat the expensive method of moments (MoM) solution even when the cavity is modified only slightly. In this Letter, the efficient method based on the partitioned‐inverse formula and the Sherman–Morrison–Woodbury formula is employed to address this problem. It can avoid the repeated MoM direct solution. We only need to solve the lower‐upper (LU) decomposition of the impedance matrix of the original cavity, and can efficiently derive the solution of the modified cavities via matrix identities without loss of accuracy. Numerical results are given to demonstrate the performance of the proposed approach.